The influence of menstrual cycle phase on neuromuscular performance and subjective perception of effort in elite football players - Romero-Moraleda, Blanca; Morencos-Martínez, Esther; Varón, Patricia; Lara, Beatriz; Jiménez-Ormeño, Ester; Peinado, Ana B.; González-García, Jaime (Biology of Sport, 2025)
This study aimed to investigate the potential fluctuations in neuromuscular performance and subjective perception of effort during three different phases of the menstrual cycle. Fifteen elite female football players (age: 23.47±6.14) volunteered to participate in the study. Tympanic temperature, saliva hormone measurement, urine concentration of the luteinizing hormone and a calendar tracker were used to verify the following phases of the menstrual cycle: early follicular phase (EFP), late follicular phase (LFP), and mid-luteal phase (MLP). For each phase, mean concentric velocity and the rate of perceived exertion (RPE) with loads that represented 60% and 80% of their 1RM in the half-squat, deadlift and hip thrust exercises were compared. The counter-movement jump (CMJ) test was also performed. Overall, jump height, mean concentric velocity in half-squat, deadlift, and hip thrust exercises with loads at 60% and 80% RM and RPE were all similar in all menstrual cycle phases, without significant differences ( p > 0.05). The results of this investigation suggest that vertical jump, mean concentric velocity in three different exercises at different submaximal loads, and RPE for each exercise are not affected in eumenorrheic elite female football players throughout different phases of the menstrual cycle. The study indicated that lower limb mechanical performance in elite female football players remain consistent across menstrual cycle phases. Coaches can confidently monitor and optimize training without undue adjustments related to menstrual cycles.